Outer Solar System Prospective Energy and Material Resources - Badescu, Viorel; Zacny, Kris.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
The Earth has limited resources while the resources in space are virtually unlimited. Further development of humanity will require going beyond our planet and exploring of extraterrestrial bodies and their resources. This book investigates Outer Solar Systems and their prospective energy and material resources. It presents past missions and future technologies and solutions to old problems that could become reality in our life time. The book therefore is a great resource of condensed information for specialists interested in current and impending Outer Solar Systems related activities and a good starting point for space researchers, inventors, technologists and potential investors.
A Survey of Pluto's Surface Composition -- Physical Properties of Icy Materials -- Atmospheric Mining in the Outer Solar System: Resource Capturing, Storage, and Utilization -- Project VALKYRIE: Laser-powered Cryobots and Other Methods for Penetrating Deep Ice on Ocean Worlds -- Europa Drum Sampler (EDuS) -- Drilling mechanisms using piezoelectric actuators developed at Jet Propulsion Laboratories -- Ultrasonically-assisted penetration of granular and cemented materials -- Flight in the Outer Solar System and Interstellar Travel -- Triton Hopper: Exploring Neptune's Captured Kuiper Belt Object -- Sub-Ice Autonomous Underwater Vehicle Architectures for Ocean World Exploration and Life Search -- Titan Submarine -- WindBots: A Concept for Persistent In-Situ Science Explorers for Gas Giants -- Enceladus Vent Explorer Concept -- Prospect of Exploration and Exploitation of Kuiper Belt Object Resources in the Future -- Outer Solar System - Sample Return Mission by an Unmanned Interplanetary Spaceship UNIS -- Spacecraft Power System Considerations for the Far Reaches of the Solar System -- Hybrid nuclear spacecraft for the outer planets -- Exploration of the Outer Solar System: Missions and their Power Systems -- Multi-Rendezvous Solar Electric Propulsion Mission Opportunities to Jupiter Trojans -- Implausible, Yet Intriguing:  Business in the Outer Solar System -- Sources of Energy in the Outer Solar System.
Keywords: Electric power production; Solar system; Planetary science; Aerospace engineering; Astronautics; Astronomy -- Observations; Electrical Power Engineering; Mechanical Power Engineering; Space Physics; Planetary Science; Aerospace Technology and Astronautics; Astronomy, Observations and Techniques